THE ANALYSIS OF FACTORS AFFECTING FIRM VALUE - Ilhami, Susanti Dwi; Dyayanti, Sukris (Jurnal Mebis, 2024)
This study uses firm size, profitability, and capital structure variables on firm value. Determining the effect of size, profitability, and also capital structure on the firm value of food and beverage companies listed on the Indonesia Stock Exchange for the period 2018-2022 was the objective for the research. The population in this research used 20 food and beverage firms, with 12 firms as the sample size. This research implemented the analysis techniques of multiple linear regression for processing the data. The finding for this research found that (1) firm size has a positive no significant effect on firm value. (2) profitability has a positive no significant effect on firm value. (3) capital structure has a negative no significant effect on firm value.